Managing the development of pedagogical competences - Labak, Irena (Array, 2020)
Competence implies the ability or expertise of an individual to successfully master a variety of goals. There are general competences that are transferrable and professionindependent, and specific, professiondependent competences. Everyone uses both specific and general competences in their personal and professional life. Teachers need numerous competences to be able to do their job, and these are called pedagogical competences. Pedagogical competences, like other competences, are not static and cannot fully be acquired during professional education. Moreover, they are dynamic and require a lifetime of dedication, development, and growth. This paper discusses and suggests methods for teachers to monitor and plan the development of pedagogical competences in their everyday work so as not to become passive observers in their professional growth. The paper suggests a model of iterative reflections that gather feedback on the effectiveness of development and identifies novel requirements for continuous development.